2018
DOI: 10.1097/md.0000000000010573
|View full text |Cite
|
Sign up to set email alerts
|

HIV prevalence among men who have sex with men in Brazil

Abstract: This paper reports human immuno-deficiency virus (HIV) prevalence in the 2nd National Biological and Behavioral Surveillance Survey (BBSS) among men who have sex with men (MSM) in 12 cities in Brazil using respondent-driven sampling (RDS).Following formative research, RDS was applied in 12 cities in the 5 macroregions of Brazil between June and December 2016 to recruit MSM for BBSS. The target sample size was 350 per city. Five to 6 seeds were initially selected to initiate recruitment and coupons and intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(67 citation statements)
references
References 37 publications
3
50
0
14
Order By: Relevance
“…A survey conducted in 12 Brazilian capitals in 2016 found that 18.4% of MSM surveyed were infected with HIV. The survey was conducted among MSM aged 18 years and over, 58.3% of them younger than 25 years of age 24 . Sperhacke et al 1 identified that in 2016 the prevalence of HIV among Brazilian conscripts who declared themselves as MSM was 1.32%, while for the total sample the prevalence was 0.12%.…”
Section: Condom Use In Every Sexual Intercourse With Occasional Partnmentioning
confidence: 99%
“…A survey conducted in 12 Brazilian capitals in 2016 found that 18.4% of MSM surveyed were infected with HIV. The survey was conducted among MSM aged 18 years and over, 58.3% of them younger than 25 years of age 24 . Sperhacke et al 1 identified that in 2016 the prevalence of HIV among Brazilian conscripts who declared themselves as MSM was 1.32%, while for the total sample the prevalence was 0.12%.…”
Section: Condom Use In Every Sexual Intercourse With Occasional Partnmentioning
confidence: 99%
“…In Brazil, about 883,000 people were estimated to be living with HIV as of June 2017 4 , with a high HIV seroprevalence among MSM (17.5% in 2016) 5 . In addition, MSM face barriers in the HIV continuum care, from early diagnosis to attaining viral load suppression 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, HIV prevalence among the general population is below 0.6% and it is estimated that AIDS cases among Brazilians reached 882,810 by June 2017 (Brasil, 2017). HIV prevalence is higher in key populations at risk, for example 17.5% in men who have sex with men (MSM) (Kerr et al, 2018). The detection rate of AIDS has been falling steadily in Brazil in recent years.…”
Section: Introductionmentioning
confidence: 99%